Star wars, clone wars. Volume 2, Victories and sacrifices - Wayne, Joe; Digital Chameleon (Firm) (Milwaukie, OR : Dark Horse Books, 2003)
A Star Wars graphic novel in which, in the midst of the Clone Wars, Obi-Wan and Anakin head to one of the moons of Naboo to stop Separatists from staging a genocidal attack on Padmé's home world.
"This volume collects Star wars: Republic #51-53 and Jedi: Shaak Ti"--T.p. verso.
5.8
Young Adult
Keywords: Kenobi, Obi-Wan (Fictitious character) -- Fiction; Vader, Darth (Fictitious character) -- Fiction; Good and evil -- Fiction; Cartoons and comics; Kenobi, Obi-Wan (Fictitious character) -- Fiction; Vader, Darth (Fictitious character) -- Fiction; Good and evil -- Fiction; Comic books, strips, etc; Graphic novels